Effects of Large Openings in the Shear Zone of Reinforced Concrete Beams - Chin, Siew Choo; Shafiq, Nasir; Nuruddin, Muhd Fadhil (Construction Research Institute of Malaysia, 2013)
Openings are often provided in reinforced concrete (RC) beams to facilitate the passage of utility pipes and ducts to accommodate essential services in buildings either commercial or residential.